Preventing behavioural and emotional problems in children who have a developmental disability: A public health approach - Mazzucchelli, Trevor; Sanders, M. (Pergamon, 2011)
Children with developmental disabilities are at substantially greater risk of developing emotional and behavioural problems compared to their typically developing peers. While the quality of parenting that children receive has a major effect on their development, empirically supported parenting programs reach relatively few parents. A recent trend in parenting intervention research has been the adoption of a public health approach to improve the quality of parenting at a population level. This has involved delivering parenting interventions on a large scale and in a cost-effective manner. Such trials have been demonstrated to reduce negative parenting practices, prevent child maltreatment, and reduce child behavioural and emotional problems. However, these trials have been restricted to parents of children who are developing typically. This paper explores the rational for the extension of a population health approach to parenting interventions for children with developmental disabilities. It is argued that a population-based implementation and evaluation trial of an empirically supported system of interventions is needed to determine whether this approach is viable and can have a positive impact on parents and their children in a disability context. The Stepping Stones Triple P—Positive Parenting Program is presented as an example of a parenting intervention that satisfies the requirements for such a trial. Tasks and challenges of such a trial are discussed.